2019
DOI: 10.18203/2320-6012.ijrms20191302
|View full text |Cite
|
Sign up to set email alerts
|

A clinico-pathological study of lichenoid tissue reactions/interface dermatitis

Abstract: Background: Lichenoid tissue reaction/Interface dermatitis (LTR/ID) refers to a number of clinically diverse, poorly understood and relatively uncommon inflammatory skin diseases. This study was done to understand the histopathological features of lichenoid tissue reactions in skin biopsies and to assess the concordance and disparity between the clinical and histopathological diagnosis of variants of the same.Methods: It was a 3½ years study from January 2014 to June 2017 in the department of Pathology, KIMS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
(50 reference statements)
6
3
0
Order By: Relevance
“…Among LP and its variants-classical lichen planus was the most common. This is in concordance with the studies done by Kumar et al, Chauhan et al and Dixit et al 5,8,14 Lichen planopilaris was the second most common LP variant in our study followed by lichen planus pigmentosus and hypertrophic LP with equal frequency. But other studies like Chauhan et al and Banushree et al reported lichen planus pigmentosus as the second most common LP variant.…”
Section: Spectrum Of Diseases Under Interface Dermatitissupporting
confidence: 94%
See 2 more Smart Citations
“…Among LP and its variants-classical lichen planus was the most common. This is in concordance with the studies done by Kumar et al, Chauhan et al and Dixit et al 5,8,14 Lichen planopilaris was the second most common LP variant in our study followed by lichen planus pigmentosus and hypertrophic LP with equal frequency. But other studies like Chauhan et al and Banushree et al reported lichen planus pigmentosus as the second most common LP variant.…”
Section: Spectrum Of Diseases Under Interface Dermatitissupporting
confidence: 94%
“…7 In this study, the most common site involved was legs (49%). This is similar to studies done by Dixit et al, Khaled et al, and Parihar et al [14][15][16]…”
Section: Correlation Of Clinical and Histopathological Diagnosissupporting
confidence: 92%
See 1 more Smart Citation
“…The mean age of patients was 43.02 years while the mean age was below 43 years in CLP and over 42 years in OLP. Numerous similar studies have reported LP being more common in women (15)(16)(17), although few studies have found that LP is more prevalent in men (13,18,19). The age category of patients in most studies was the fifth and sixth decades of life, and the mean age in the studies of Pakfetrat et al, Ramalingam et al and Silverman et al were reported to be 41.6, 43.2 and 52 years, respectively, similar to our results (13,20,21).…”
Section: Discussionsupporting
confidence: 90%
“…2 Findings such as infiltrates of neutrophils, eosinophils, and plasma cells are rare but may still be seen in lichenoid tissue reactions. 8,12 Additional findings of hyalinized vessels and sub-epidermal extravasation of erythrocytes may be seen in purpuric lichen nitidus. In our patient, such changes were attributed to thrombocytopenia, a common finding in acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%